Systematic Literature Review Model Matematika Kompartemen pada Penyakit dan Kontagion Sosial - Gilang Primajati; M. Gunawan Supiarmo (Griya Journal of Mathematics Education and Application, 2026)
Epidemic-type mathematical compartmental models are no longer limited to biological infectious diseases; they are increasingly adapted to behavioral and social contagion phenomena. This study aimed to systematically review the use of SIR, SEIR, SEIRS, and modified compartmental models in infectious disease transmission and social phenomena. A systematic literature review was conducted by screening 24 full-text articles collected from journal databases and publisher repositories from 2020 to 2026. Eighteen primary modelling studies were included in the main synthesis, while six review or guideline articles were used as theoretical and methodological support. Data were extracted on model type, domain, compartments, data source, mathematical analysis, simulation method, software, and major findings. The reviewed infectious disease studies addressed tuberculosis, malaria, COVID-19, and typhus, whereas social-domain studies covered online game addiction, social media addiction (TikTok), online gambling, gambling crime, and impulsive buying. SEIR was the most frequent structure, followed by SEIRS and SIR. Most studies calculated equilibrium points and the basic reproduction number; fewer studies reported sensitivity analysis, parameter calibration, uncertainty analysis, or empirical validation. The findings indicate that compartmental models are flexible analytical tools across biological and social systems, but future studies need stronger reporting transparency, parameter justification, validation, and reproducible simulation procedures.